A revision of the genus Tineovertex Moriuti (Insecta: Lepidoptera: Tineidae), with descriptions of five new species - Huang, Guo-Hua; Hirowatari, Toshiya; Wang, Min (Zootaxa, 2011)
The genus Tineovertex Moriuti, 1982 is revised. Eleven species are recognized, including five new ones: T. hamoides, sp. nov., from Malaysia; T. expansa, sp. nov., from Malaysia and Brunei; T. fibriformis, sp. nov., from Malaysia; T. thailandia, sp. nov., from Thailand; and T. elongata, sp. nov., from China and Thailand. Adults and genitalia of all species are illustrated, and a key to the species is provided. Types of the new species are deposited in Hunan Agricultural University, Changsha, Hunan, China; Osaka Prefecture University, Sakai, Osaka, Japan; and The Natural History Museum, London, UK.